3-Snip Punctoplasty with Silicone Tube Implantation: A Simple Procedure For Punctal Disorders - R Wattimena, Aisyah Amelia Zulkarnaen; Andi Pratiwi; Pagarra, Halimah; Suliati P Amir; Syukriah Sofyan (Majalah Oftalmologi Indonesia, 2026)
Introduction: Punctal or canalicular atresia is a rare disorder in which an intact epithelial layer covers the punctum, impairing tear drainage and causing epiphora, especially in lower punctal atresia. Less frequently, canalicular atresia occurs. Standard management involves probing, irrigation, and silicone tube insertion. Case Report: In two cases, an 8-year-old and a 30-year-old female presented with lifelong tearing and discharge from the left eye. Ophthalmic examination revealed imperforate superior and inferior lacrimal puncta, and the Dye Disappearance Test (DDT) confirmed reduced tear drainage, leading to a diagnosis of punctal atresia. In a third case, a 40-year-old female experienced a painful, red lump on the right medial lower eyelid over a three-month period. Palpation produced yellowish discharge, and examination revealed a hyperemic mass with granulomas around the punctum, consistent with chronic canaliculitis. All three patients underwent a 3-snip punctoplasty with silicone tube implantation using a round-tip pigtail probe. Discussion: The 3-snip procedure is a minimally invasive and effective treatment for punctal disorders. It involves one basal cut and two vertical incisions along the canaliculus. Although canaliculotomy with curettage can lead to fistula formation, the use of a silicone tube helps prevent this complication. At the three-month follow-up, all patients demonstrated functional tear drainage and normal DDT results. Conclusion: The 3-snip procedure with silicone tube implantation offers favorable functional and cosmetic outcomes. It is a simple and viable option for ophthalmologists in resource-limited settings, ensuring improvement in tear drainage without symptom recurrence.